IRIS: ALLOCYCLIC SEGMENTS AS CHROMOSOME MARKERS? - COLASANTE, M.; VOSA, C.G. (Annali di Botanica, 2000)
Besides the linear differentiation of chromosomes, obtained by various methods including C banding, Q-banding llild G- banding, a type of differentiation is sometimes visible after Donnal fixation and Feulgen staining. Such differential segments are found in the chromosomes of many bulbous and rhizomatous Iris species and appear to be species and population specific. Chromosome analysis of several Irises has shown that there is some variation in the length and distribution of the AC-segmenl~ in different species and occasionally also in different populations of the same homeologous chromosomes. Therefore the AC-segments could be used as markers Lo eluddate the ancestry ofIris natural hybrids.